Insulin resistance and lipid profiles in HIVinfected Thai children receiving lopinavir/ritonavir-based highly active antiretroviral therapy - Prapai Dejkhamron (2018)
Background: Lopinavir/ritonavir (LPV/r) is associated with insulin resistance (IR). We aim to determine the prevalence of IR, dyslipidemia and their inter-relationships with adipokines in HIV-infected children treated with LPV/r-based highly active antiretroviral therapy (HAART). Methods: Twenty-eight children were enrolled. Fasting glucose, insulin, lipid profiles, adipokines, and oral glucose tolerance tests were performed. Results: The prevalence of IR, pre-diabetes mellitus, and hypertriglyceridemia was 42.9(12/28), 10.7(3/28), and 75.0(21/28)% respectively. No case met the definition for diabetes mellitus (DM) and lipodystrophy. Children with IR had higher BMI z-score, triglyceride levels but unchanged leptin or adiponectin levels compared to those without IR. Longer duration of LPV/r-based HAART was associated with increased levels of triglyceride and total cholesterol. Conclusions: We describe high prevalence of IR, prediabetes mellitus, and dyslipidemia among HIV-infected children receiving LPV/r-based HAART. Pre-diabetes mellitus or DM or IR screening might be important for early diagnosis and intervention in these children.